The Off-Label Use of a Lumen-Apposing Metal Stent (LAMS) for a Benign Colon Anastomotic Stricture Causing Recurrent Bowel Obstruction in a Patient with Keloids. (5th April 2021) - Coles, Michael; Uy, Pearl; Madray, Victoria; Yap, John Erikson; Sridhar, Subbaramiah
Abstract : Anastomotic strictures are a known complication of colorectal surgery. Despite a wide range of medical devices that have been deployed for this complication, outcomes remain challenging. Lumen-apposing metal stents (LAMSs) have recently emerged as a potentially superior therapeutic option. We herein report a patient with a past medical history of pT3, N0 adenocarcinoma of the colon with anastomotic stricture recurrence who underwent successful placement of an LAMS. We suggest that patients with a predisposition for keloid formation or fibrosis-prone anastomotic wound healing should be considered for LAMS deployment early in the treatment course.